Plant design for the manufacture of Carbon black from heavy fuel oil - Cruz, Elmer R.; Ramirez, Benjamin C. Jr.; Sana, Felix J. (Diliman, Quezon City College of Engineering, 1966)
The proposed plant site will be located in San Juan, Batangas. It will cover a total land area of about 8,350 square meters. The needed equipment and machinery cost about P1,280,000. Fixed capital investment amounts to P2,970,000 and the required operating cost is P3,273,510. The plant will be handling 10,320,000 pounds of fuel oil and 24,480,000 of heavy fuel oil per year. The design capacity of the plant is 20,300,000 pounds of carbon black annually and plant will be operating 24 hours a day and 300 days a year. From the economic evaluation of the project the break even point is 17 percent of the total capacity. Pay off time is about 1.28 years.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories--Design and construction; Chemical plants; Carbon-black industry